RE-INTERPRETASI NAMA CANDI BOROBUDUR - Titi Surti Nastiti (Badan Riset dan Inovasi Nasional, 2018)
Abstract. Re-Interpretation the Name of Borobudur Temple. Borobudur temple is the largest Mahāyana Buddhist temple in Indonesia built in the 8th century. The origin of the name Borobudur is still debated until today, therefore it is necessary to review the origin of the name of Borobudur. Thera are plenty of scholars from Indonesia and the Netherlands that hypothesised around the origin of the name. A few scholars thought the name originated from the word boro which means monastery and there is no agreement yet on the definitation of the word